Not all Perfectionists Are as They Are Assessed: An Investigation of the Psychometric Properties of the Perfectionism Inventory in the Teaching Profession - Samfira, Elena Mirela; Maricuţoiu, Laurenţiu P. (Frontiers in Psychology, 2021)
Perfectionism has been studied for almost 30 years. In the present study, we investigated the internal validity of The Perfectionism Inventory (PI - Hill et al., 2004) in an occupation that encourages perfectionistic tendencies in own behavior or in students’ behavior. We collected data from a large sample of schoolteachers (N = 633, 81.18% female, 63.02% from urban areas, 46.66% from secondary schools, mean age = 42.11 years) recruited using a snowball sampling approach, and we analyzed the factor structure of the PI using confirmatory factor analyses. We found that the 8-factor structure of PI provided a reasonable fit (RMSEA = .055, 90% CI = [.053-.057]; SRMR = .071). However, additional analyses revealed problematic divergent validity only in the case of the scales associated with Self-Evaluative Perfectionism, not in the case of the scales associated with Conscientious Perfectionism. We found that teachers displayed distinguishably different forms of perfectionism only when it referred to own person, not when it referred to perfectionism imposed to others. Based on these findings, we suggested that the PI could provide a useful framework for investigating the role of conscientious-related forms of perfectionism in the development of teacher beliefs regarding their school behavior.